PERANCANGAN PEMELIHARAAN POMPA AIR DI KAMPUS POLMAN BABEL MENGGUNAKAN METODE CONDITION-BASED MONITORING - Iwan Putra, Nadi; Pramono, Edi; Feriadi, Indra; Rivai, Muhammad (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Every time a water pump breaks down on the Polmanbabel Campus, it disrupts the smooth operation and service to employees and students. This project aims to design pump maintenance on the Polmanbabel campus using a condition-based monitoring (CBM) method. The project implementation method is carried out by identifying equipment, selecting condition parameters to be monitored, designing monitoring cards, and testing. The test results show that the monitored pump condition parameters consist of temperature, vibration, pressure, monitoring card instruments can be applied effectively to monitor pump operating conditions.